Lingua revolution and human civilization (special Season) - Yaacob, Solehah@Nik Najah Fadilah (2016)
After the mega explosion of the Big Bang, the planet Earth became divided into two parts, namely the earth’s surface and the sky, each of which is composed of seven layers (as mentioned in the Quran, Torah and Gospel). The time when life came into existence on this planet is known as the Paleozoic era, and at that time the situation was quite calm, with plants that were non-flowering, like moss that flourished in swamps and there was no sound of birds chirping It was quite lonely with just small animals like small fish, lizards, leaches, frogs, dragonflies and the like. Then the ecology of the earth began to change once the Mesozoic era began, or specifically the Reptilian era, where dinosaurs and huge ancient animals came into existence. At that time, the world was filled with a thick wilderness. However, this era is said to have come to an end when an asteroid collided with the earth, creating a great explosion. The impact of this collision is believed to have caused the extinction of an enormous population of animals that existed on earth, mainly from the herbivores and carnivores. It is also believed that several types of animals especially those species which fed on saprophytic organisms, such as dragonflies, frogs and lizards, had a better chance of survival. Then the prophet Adam (A.S) and Hawa (Eve) were sent down to earth as soon as the wrath of Allah (SWT) had become a starting point for the world to be a festival of life, wherein a variety of incidents had been recorded. The spreading of the human descendants on earth started with the descendants of Adam, i.e. Shith and his partner, Hazura. The climatic and weather conditions of the time are said to be the main factor for the migration of man to various regions of Asia, Europe, Africa and the Arabian Peninsula. This theory is also supported by the discovery of “Perak Man” and “Perak Women” in the state of Perak, Malaysia. Even though the story of Idris (A.S) is rarely mentioned in history due to a scarcity of authentic sources of information, according to historians, the story of Noah and the Great deluge is of the opposite nature. 5 That story is not only narrated in the Holy Quran, Torah, and the Gospels, but there are also stone inscriptions that tell of the incident. Linguists, historians and archaeologists are still on the search for the answers as to whether the story of the flood that is mentioned on the stones, i.e. the Epic of Gilgamesh, which was written using Mismariah script in the Accadian language is telling the same story as in the Torah. The story of the flood, which is found on the eleventh tablet resembles the story of the Great Deluge that is found in the Torah. Historians believe that the story of Noah’s flood happened around 4800 BC, whereas the inscription of the Epic of Gilgamesh is found to be from 4000 BC, whilst the time of Moses (A.S.) is said to be from 1000 -1200 BC. Language historians are of the opinion that there is a chance that the story of the flood that is told in the Torah is written based on the same story that is told in the Epic of Gilgamesh, based on several similarities that are found in both stories. For instance, both stories tell that after a few days after the flood, the main character, also known as Utunabishtim had set free several birds through the arc’s window on the seventh day on the arc. However, three days later, the birds returned to the ship indicating that there was no place to land on as everything was under water. Then, “Utunabishtim” released the birds again, and the same incident was repeated as the birds returned to the arc. For a third time, he released the birds but none of them returned to the arc, and thus “Utunabishtim” understood that the water had started to recede and that there was land to stop at. If this opinion is correct, then it becomes evidence that the detailing of the Great Deluge that is mentioned in the Torah is a recording done by man and is not a revelation from God! Aside from that, there are also numerous names of Arab tribes that had appeared Aad and Thamud that were erased from the genealogy tree of the Torah, when explaining about the descendants of Noah. Amongst the children of Aram (grandson of Noah) that were lost are Aus, Ghasir, and Jaser, or as they are known by historians as al-Arab al-Baidah al-Ula (The First Lost Arab) that is the origins of Aad and Thamud who are al-Arab al-Baidah (The Lost Arab). Furthermore, the story of Ibrahim (A.S) who has a third wife is also discussed, aside from Sarah (who is his uncle Haran’s daughter) and 6 Hagar (previously a palace maid of the Pharoah), while also telling about his relative, Luth (Sarah’s relative) as well as the tale of the destruction of Pompeii. The tale of the greatness of King Sargon and King Hamurabbi will also be featured based on clues that are found on the inscriptions and ancient Jewish scriptures. This book also touches on the story of the famous Code of Hammurabi that is said to be similar to the Code of Moses so much so that some language historians believe that the Code of Moses appeared as a product of the Code of Hammurabi that was written 800 years before it. If this is true, then it would be proven again that Jewish Rabbis had written the Torah on their own by taking information from the Code of Hammurabi without revealing their source of reference. This theory is partially true, as it is said that the original tablet that contained the Code of Moses had been destroyed by Moses himself after he went down from Tur Sina, as he was deeply angered by his people who were worshipping a golden cow. Even though some opine that it is still around and could have been used once the broken pieces are pieced together, the incident where Moses and his followers were lost in the Tieh desert on their way to Palestine for 40 years, as well as the wars that sparked then had increased the probability that the tablet of the Code of Moses were destroyed. Furthermore, this book also discusses the language that was spoken by Moses and the language that was used to write the Code of Moses. This discussion is important as Western linguists had claimed that Aramaic was the lingua franca between the 17th BC up to the first century BC. However, what about the claim that the original language of the Torah and the Gospels being Hebrew? Here, there is a theory that Jewish Rabbis at the time had mixed Hebrew into Aramaic and Phoenician in their writings in the Torah. Verily, the discussion on languages and the changes in writing is the basic story of this book that relies on a case study approach, through the stories of the prophets and written evidence on inscribed stones. The discussion is then taken further with a description of the relationship of Palestine and the Greeks, that is , it is believed that Greek writing was initially written from right to left due to the influence of Phoenician (a west Semitic 7 language), before it was changed to be from left to right. There exists similarities as well on the writing of the poems of the Iliad and Odyssey that were composed by Homer in 750 BC with Arab poems, such as in the rhyme that indicate that they were not written but rather simply memorized. Apart from that, the discussions in this book also touch on governments that are lesser featured in ancient history such as the government of Aram, Hammurabi, Assyria, Nabatean, Qaidar, Ghasasanah, and Palmyra that then lead us to the mention of the names of great Arab dynasties. Amongst them the female ruler Zenobia or as some language historians state her name to be As-Sabba’ who was well-known for her wisdom in managing her kingdom and learning several foreign languages including Greek and Latin. Clues that exists on inscriptions had become important sources of history and were displayed widely throughout this book to fortify the stories; for example the inscribed stones of Imru` al-Qais and Ummu Jamal that were used as strong pieces of evidence that show that the evolution in Arabic writing had started a long time ago. Language historians believe that the evolution of writing and words of a language occur alongside changes in the thinking of the race and society of that time. This then brings us to the next discussion on the word ‘Allah’ as well as the history of its writing. The holy scriptures that were sent down before the Quran i.e. the Torah, Gospels, and Psalms has used a language that suited the strength of the thinking of the people that were receiving them. And Allah knows best.